Pemanfaatan Beton Ringan Dari Agregat Pumice Dengan Penambahan Abu Sekam Padi Sebagai Pengganti Beton Biasa Untuk Struktur Bangunan - Dedi Budi Setiawan; Sukoyo Sukoyo (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2012)
Light concrete is one of concrete type which more and more applied during now. In Europe and United States light concrete have been long enough and many utilized. Compressive strength yielded by lower light concrete than compressive strengths yielded by ordinary concrete. But, weakness found on light concrete can be overcome with excess obtained that is lighter wight. Causing enables once for high rise building sewer structures of height. In this research, more pointly weighs against at light concrete with aggregate pumice with addition of paddy chaff ash. Aggregate applied with light material that is pumice and addition of paddy chaff ash to increase compress and exploits raffle around rural public. Paddy chaff ash is material having property as puzzolan. Weakness of light concrete having compressive strength lower than ordinary concrete tried improved with addition of usage of paddy chaff ash having property pozolan. Concrete pumice with comparison ( 1 : 2 : 2) with addition of chaff ash, optimum condition reached at chaff ash content 10% , this still possibly increasing but its the increasing of on the wane.